2016
DOI: 10.12669/pjms.323.9895
|View full text |Cite
|
Sign up to set email alerts
|

The healing effect of bone marrow-derived stem cells in acute radiation syndrome

Abstract: Objectives:To determine the effect of bone marrow-derived mesenchymal stem cells (BMSCs) on regeneration of bone marrow and intestinal tissue and survival rate in experimental mice with acute radiation syndrome (ARS).Methods:Forty mice were randomly divided into two equal groups of A receiving no BMSC transplantation and B receiving BMSCs. BMSCs were isolated from the bone marrow and cultured in DMEM media. Both groups were irradiated with 10 Gy (dose rate 0.28 Gy/ min) 60CO during 35 minutes with a field size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Studies have reported that bone marrow-derived mesenchymal stem cells mitigate ARS. 16,17 Other approaches employing placental-derived and Wharton's jelly derived mesenchymal stem cells rescue from radiation by regenerating damaged bone marrow from TBI. [18][19][20] Low yield and difficulty in harvest and mass production for stockpiling are some of the drawbacks associated with the therapeutic application of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that bone marrow-derived mesenchymal stem cells mitigate ARS. 16,17 Other approaches employing placental-derived and Wharton's jelly derived mesenchymal stem cells rescue from radiation by regenerating damaged bone marrow from TBI. [18][19][20] Low yield and difficulty in harvest and mass production for stockpiling are some of the drawbacks associated with the therapeutic application of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enhancement of the body resistance to radiation and improvement of treatment strategies post-radiation have been got great attention. Bone marrow transplantation (BMT) is one of the major choices in saving life and repairing the damaged organs or tissues particularly in high-dose radiation, and there is a tremendous amount of effort in BMT studies in human or animal system [ 3 , 9 11 ]. Nevertheless, the specific type of contributing cells and their underlying mechanism in tissue repair in response to radiation is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in the setting of advanced inflammatory bowel disease, marked denudation of the mucosal epithelium occurs, yet epithelial healing is still achieved, even though the adjacent epithelial cells may be completely lost 7 . Such observations raise the possibility that previously unrecognized pathways could play key roles in intestinal mucosal healing after mucosal injury, especially under conditions in which proliferation and restitution are unlikely to be effective 8, 9, 10, 11 . In this regard, previous authors have suggested the possibility that circulating, extra-intestinal cells can migrate to sites of intestinal injury where they may contribute – either directly or in a paracrine fashion – to the mucosal healing response 12, 13 .…”
Section: Introductionmentioning
confidence: 99%